2007
DOI: 10.1074/jbc.m609101200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Constitutively Active STAT3 Can Replicate the Cytokine-suppressive Activity of Interleukin-10 in Human Primary Macrophages

Abstract: There is general agreement that signal transducer and activation of transcription 3 (STAT3) is required to mediate the antiinflammatory activities of interleukin (IL)-10. However, STAT3 is activated by multiple factors that do not share the anti-inflammatory activity of IL-10. The question remains whether STAT3 is sufficient for the anti-inflammatory effects or whether there are other signals required, as had been suggested previously. We set out to map the human IL-10 receptor and to identify the key elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 62 publications
3
81
0
Order By: Relevance
“…The interaction of apoA-I with ABCA1 in macrophages suppressed the lysopolysaccaride-induced secretion of the inflammatory cytokines such as interleukin-1β, interleukin-6, and tumor necrosis factor-α, which was reversed by silencing STAT3 or ABCA1. Thus, the apoA-I/ABCA1 interaction activates the JAK2/STAT3 pathway (57), which is antiinflammatory in macrophages (69)(70)(71)(72). Our studies also demonstrate IFN-γ may first downregulate expression of LXRα through the JAK/STAT1 signaling pathway and then decrease expression of ABCA1 and cholesterol efflux in THP-1 macrophage-derived foam cells (71,73).…”
Section: +mentioning
confidence: 67%
“…The interaction of apoA-I with ABCA1 in macrophages suppressed the lysopolysaccaride-induced secretion of the inflammatory cytokines such as interleukin-1β, interleukin-6, and tumor necrosis factor-α, which was reversed by silencing STAT3 or ABCA1. Thus, the apoA-I/ABCA1 interaction activates the JAK2/STAT3 pathway (57), which is antiinflammatory in macrophages (69)(70)(71)(72). Our studies also demonstrate IFN-γ may first downregulate expression of LXRα through the JAK/STAT1 signaling pathway and then decrease expression of ABCA1 and cholesterol efflux in THP-1 macrophage-derived foam cells (71,73).…”
Section: +mentioning
confidence: 67%
“…The STAT3 pathway is well known to have an anti-inflammatory function in macrophages (25)(26)(27). In fact, constitutive activation of STAT3 is sufficient to block most of the activated macrophage production of inflammatory cytokines (28). We have shown that the interaction of apoA-I or its mimetic peptides with ABCA1-expressing macrophages activates STAT3 and markedly suppresses the expression of proinflammatory cytokines (24).…”
Section: Immunoblots and Immunoprecipitationmentioning
confidence: 86%
“…The major function of IL-10 is to negatively regulate inflammatory responses from activated macrophages and dendritic cells (63). The inhibitory effects of IL-10 are mediated solely by STAT3 and are indirect (63)(64)(65)(66). That is, IL-10-mediated activation of STAT3 targets one or more STAT3-regulated genes whose products are responsible for inhibiting inflammatory gene expression at the level of transcription.…”
Section: Is There Functional Equivalence In Signaling From Receptors mentioning
confidence: 99%